2017
DOI: 10.1371/journal.pone.0179893
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the 19S regulatory particle ATPase subunit, Rpt6, modifies susceptibility to proteotoxic stress and protein aggregation

Abstract: The ubiquitin proteasome system (UPS) is a highly conserved and tightly regulated biochemical pathway that degrades the majority of proteins in eukaryotic cells. Importantly, the UPS is responsible for counteracting altered protein homeostasis induced by a variety of proteotoxic stresses. We previously reported that Rpt6, the ATPase subunit of the 19S regulatory particle (RP) of the 26S proteasome, is phosphorylated in mammalian neurons at serine 120 in response to neuronal activity. Furthermore, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…It may be likely that TOR is involved in phosphorylating some component(s) of the 19S proteasome subcomplex to regulate its function in promoting recruitment of NuA4 KAT to the UASs of the RP genes. In support of this possibility, recent studies (55,56) demonstrated the phosphorylation of several components (e.g., Rpn1p, Rpt2p, Rpt3p, Rpt5p, and Rpt6p) of the 19S proteasome subcomplex. Such phosphorylation has been implicated in facilitating the ATPase activity of the 19S proteasome subcomplex and its assembly (55,57) and hence function (since previous studies demonstrated the role of the 19S ATPases in stimulation of the interaction between activator and coactivator [1,14,37,44]).…”
Section: Discussionmentioning
confidence: 86%
“…It may be likely that TOR is involved in phosphorylating some component(s) of the 19S proteasome subcomplex to regulate its function in promoting recruitment of NuA4 KAT to the UASs of the RP genes. In support of this possibility, recent studies (55,56) demonstrated the phosphorylation of several components (e.g., Rpn1p, Rpt2p, Rpt3p, Rpt5p, and Rpt6p) of the 19S proteasome subcomplex. Such phosphorylation has been implicated in facilitating the ATPase activity of the 19S proteasome subcomplex and its assembly (55,57) and hence function (since previous studies demonstrated the role of the 19S ATPases in stimulation of the interaction between activator and coactivator [1,14,37,44]).…”
Section: Discussionmentioning
confidence: 86%
“…Post-translational modifications, such as phosphorylation, regulate the activity of nuclear proteasomes (Bose et al, 2004; Sha et al, 2011). Phosphorylation of proteasomal subunits enhances proteasomal proteolysis of misfolded proteins and modifies the cellular susceptibility to proteotoxic stress and protein aggregation (Collins and Goldberg, 2017; Marquez-Lona et al, 2017). We observed that PSG formation is disturbed in snf1 Δ null mutants.…”
Section: Unexplored Topics In Proteasome Transport and Psg Formationmentioning
confidence: 99%
“…For instance, PKA-dependent proteasome phosphorylation has been shown to be a positive regulator of 26S proteasome function in several cell lines [41,43], primary neuronal cells [40,50,51], and also in vivo in mouse models of FTD [25] and HD [49]. Moreover, other kinases have been shown to exert a similar effect on 26S proteasome hydrolytic capacity, including CaMKIIα in primary neuronal cultures [3739,45], DYRK2 in a breast cancer mouse model and cell lines [48], and PKG in a UPS reporter (GFP-degron) mouse model [44].…”
Section: Direct Activation Of 26s Proteasome Functionmentioning
confidence: 99%
“…Indeed, the recruitment of 26S proteasomes to dendritic spines can promote local protein degradation, an important regulatory mechanism for synaptic remodeling and for forming synaptic connections [3739,45]. In addition, proteasome activity assays have shown that PKA [25,36,4042,46,49,50], CaMKIIα [38,39,51], DYRK2 [48], and PKG [44] can increase the activity of proteasome peptidases (β1, β2, and β5 subunits). In contrast to phosphorylation acting on proteasome activity directly, phosphorylation might also increase the percentage of proteasomes that are engaged in substrate processing; this speculation is based on a recent cryo-electron microscopy tomography study reporting that in healthy neurons the capacity of the proteasome system is not fully utilized [53].…”
Section: Direct Activation Of 26s Proteasome Functionmentioning
confidence: 99%